Decreased Plasma Oxytocin Levels in Patients With PTSD - Carmassi, Claudia; Marazziti, Donatella; Mucci, Federico; Della Vecchia, Alessandra; Barberi, Filippo Maria; Baroni, Stefano; Giannaccini, Gino; Palego, Lionella; Massimetti, Gabriele; Dell’Osso, Liliana (Frontiers in Psychology, 2021)
Introduction Although the pathophysiology of post-traumatic stress disorder (PTSD) is still unclear, growing preclinical evidences suggest that oxytocin (OT), a pleiotropic hormone, is possibly involved. However, direct studies on OT levels or clinical trials with this exogenous hormone in patients with PTSD led to inconsistent findings. Therefore, the aim of the present study was at exploring and comparing the plasma OT levels in a group of patients with PTSD and matched healthy subjects as the control group. Materials and Methods Twenty-six outpatients (13 men, 13 women, mean age: 40.3 ± 11.5 years) suffering from PTSD, according to the Diagnostic and Statistical Manual for Mental Disorders, fifth edition (DSM-5), and 26 healthy subjects (13 men, 13 women, mean age: 43.8 ± 12.7 years) were included. The patients were assessed through the structured clinical interview for DSM-5 research version, patient edition (SCID-I/P), and the Impact for Event Scale revised (IES-R). All fasting subjects underwent three venous blood samples for the subsequent oxytocin radioimmunoassay. We used unpaired Student’s t-test to assess OT levels and the intergroup difference of demographic characteristics, while anxiety, avoidance, and hyperarousal scores were compared among groups adjusting for the effect of gender and age by means of analysis of covariance (ANCOVA). The correlations between different variables were investigated by Pearson’s method. Results The most common traumatic events of patients with PTSD were the following: severe car accident, physical violence, sexual violence, sudden death of a loved one, and natural disaster. The IES total score was 55 ± 15. Student’s t-test revealed that the patients showed significantly lower OT levels (mean ± SD, pg/ml) than healthy control subjects (4.37 ± 1.61 vs 5.64 ± 2.17, p < 0.001). We detected no correlation between the IES total score, subscales, or single items and OT plasma levels. Again, no difference between men and women was detected in the patients’ group, while healthy control women showed higher OT levels than men. Discussion Our study, while reporting the presence of decreased plasma OT levels in outpatients with PTSD of both sexes, as compared with healthy control subjects, would support the possible involvement of OT in the pathophysiology of PTSD. However, given the complexity of the clinical picture, future investigations are necessary to better deepen the role and level of OT in PTSD.